Using Imaging Mass Cytometry to Define Cell Identities and Interactions in Human Tissues - Kakade, Vijayakumar R.; Weiss, Marlene; Cantley, Lloyd G. (Frontiers in Physiology, 2021)
In the evolving landscape of highly multiplexed imaging techniques that can be applied to study complex cellular microenvironments, this review characterizes the use of Imaging Mass Cytometry (IMC) to study the human kidney. We provide technical details for antibody validation, cell segmentation and data analysis specifically tailored to human kidney samples, and elaborate on phenotyping of kidney cell types and novel insights that IMC can provide regarding pathophysiological processes in the injured or diseased kidney. This review will provide the reader with the necessary background to understand both the power and the limitations of IMC, and thus support better perception of how IMC analysis can improve our understanding of human disease pathogenesis and can be integrated with other technologies such as single cell sequencing and proteomics to provide spatial context to cellular data.